Interfacial engineering of Fe2O3@BOC heterojunction for efficient detoxification of toxic metal and dye under visible light illumination. Issue 1 (February 2019) - Kar, Prasenjit; Jain, Pratyush; Kumar, Vishrant; Gupta, Raju Kumar
Graphical abstract: Highlights: Development of efficient heterojunction by variation of Fe2 O3 nanoparticle on BOC. Role of interface towards visible light photocatalytic activity of Cr(VI) and MB. The optimized heterojunction exhibits high activity, stability and recyclability. Investigation of mechanistic pathway and role of reactive oxygen species. Development of inexpensive prototype reactor for potential practical application. Abstract: Recent developments of small band gap semiconductor coupled bismuth carbonate (BOC) heterojunction are advantageous for photocatalysis application because of their improved solar harvesting ability and enhanced charge-carrier collection. In this work, we have developed iron (III) oxide decorated bismuth carbonate (Fe2 O3 @BOC) heterojunction via a simple two-step process. The developed heterojunction exhibits excellent photocatalytic activity towards reduction of carcinogenic and mutagenic Cr(VI) to nontoxic Cr(III) and degradation of toxic dye [methylene blue (MB)] under visible light illumination. Further investigation revealed that the loading of Fe2 O3 nanoparticles had an impact on efficient charge carrier collection at the interface of Fe2 O3 @BOC heterojunctions. The unprecedented photocatalytic activity for Fe2 O3 @BOC1 heterojunction at room temperature could be attributed due to the enhancement in light absorption ability and suppression of electron–hole pair recombination at the heterojunction interface. In addition, reduction in efficacy of the heterojunction with increase in loading of Fe2 O3 nanoparticles on BOC surface further confirms the role of interface on the modulation of photocatalytic activity. The role of photogenerated electrons and reactive oxygen species involved during photocatalytic reduction of Cr(VI) and degradation of MB was studied in detail. Moreover, recyclability experiment demonstrates that the developed photocatalyst can be reused without decay in performance. Finally, development of inexpensive prototype reactor is demonstrated towards reduction of Cr(VI) and degradation of MB under continuous flow operation. Thus, good efficacy of the developed reactor for cleaning of toxic pollutants in water makes the heterojunction (Fe2 O3 @BOC1) a promising photocatalyst for water purification in near future.